Cu and Ni Nanoparticles Deposited on ITO Electrode for Nonenzymatic Electrochemical Carbohydrates Sensor Applications. Issue 4 (1st December 2016) - He, Yingqiao; Wei, Guodong; Lin, Junhong; Sun, Mingxu; Li, Ziheng
Abstract: A novel non‐enzymatic carbohydrates sensor which was an indium tin oxide (ITO) glass electrode modified by nickel and copper nanoparticles (Cu/Ni/ITO) was developed by an electrochemical method. The crystallinity, morphology, electrochemical measurements and amperometric response of the as‐prepared ITO modified electrode were examined by the X‐ray diffraction (XRD), scanning electron microscopic (SEM), cyclic voltammetry (CV) and chronoamperometry, respectively. The Cu/Ni/ITO electrode had better electroactivity for glucose oxidation than that obtained using Cu/ITO, Ni/ITO, and Ni/Cu/ITO. The logistic regression equation, Ipa = ( A 1 – A 2 )/[1 + ( Cglucose / x 0 ) p ] + A 2, was used to fit the calibration curves of glucose aqueous solution concentrations and responsive current intensity. In research of other saccharides, such as fructose, lactose, sucrose, and maltose, which were detected by the Cu/Ni/ITO electrode, it was obvious that the Cu/Ni/ITO electrode was more sensitive to monosaccharides than disaccharides. Monosaccharides and disaccharides can be detected because the saccharides themselves had aldehyde group or be isomerized to an isomer having an aldehyde group in alkaline environment, and then aldehyde group produced carboxylic acid in the catalytic oxidation of the electrode, which lead to the change of electrode surface conductivity and the appearance of oxidation peak, and the alkaline environment further promotes the above reaction. Abstract :